Reducing Maternal Anxiety Levels Using Autogenic Relaxation During The Covid 19 Pandemic - Dwi Cindy Hardianti; Devi Mediarti; Siti Hindun (Poltekkes Kemenkes Palembang, 2021)
ABSTRACT Background: In Indonesia and even the world is experiencing the Coronavirus disease 2019 (COVID-19) pandemic. This can cause anxiety and have a negative impact on the psychology of pregnant women. Autogenic Relaxation is a form of mind body intervention, originating from within oneself that can make the mind calm, making motivational words or sentences done by imagining oneself in a calm and peaceful state, focusing on heart rate and breathing regulation can reduce anxiety levels pregnant women during the COVID-19 pandemic. Objective: To determine the Effect of Autogenic Relaxation Techniques on Anxiety Levels of Pregnant Women During the Covid-19 Pandemic At BPM Meli Rosita Palembang in 2021. Results: Statistical test results Anxiety levels before and after being given treatment with Autogenic relaxation techniques (Treatment Group) obtained p-value 0.001 (<0.05). The results of the Mann Whitney statistic test obtained a p value of 0.000 <0.05. With this it can be said that there is a difference in the Posttest of the treatment group and the control group. Because there is a significant difference, it can be said that